Biosorption potentials of sawdust in removing zinc ions from aqueous solution - Michael Ogunjobi, Kayode; Jayeola, Victor Adeoluwa; Friday Gakenou, Oluwaseun; Oluwaseun Olufemi, Opeyemi; Oluwafemi Ayanleye, Samuel; Jumoke Lawal, Kudirat (International Journal of Scientific Research and Management (IJSRM), 2021)
Timber processing industries generate enormous waste, which constitutes environmental nuisance. However, the sawdust contains several organic compounds that could actively remove heavy metal ions from an aqueous solution through the adsorption process. This study investigated the efficacy of sawdust of Albizia zygia and Gmelina arborea in removing Zinc (II) under two factors affecting adsorption, Contact time and pH. Sawdust samples were sieved through a screen size of 2.0mm, after which a portion of sawdust for each species was subject to pre-treatment by boiling while the other parts were kept as control samples (untreated). The effect of pH on the removal efficiency of the biosorbent was determined by adding 0.2g of the sawdust (treated and untreated) into six conical flasks containing the metal solution (50ppm) at different pH values. There was a significant difference in the removal efficiency of both treated and untreated samples for both species. Removal efficiency also increased with time, with maximum Zn (II) biosorption achieved at 90 minutes. Removal efficiency increased with pH and reached optimum pH of 4. Both species' maximum Zn (II) biosorption (Albizia zygia = 17.22, Gmelina arborea = 17.92) compared favourably with other biosorbent used in previous studies. From this study and based on availability, cost-effectiveness, ability to be recovered and reused, sawdust of Albizia zygia and Gmelina arborea are proven alternative adsorbents treatment of water towards ensuring that quality water is available for humans, plants, and animals.